2017
DOI: 10.21003/ea.v166-02
|View full text |Cite
|
Sign up to set email alerts
|

Econometric model of dependence between the oil prices, and the global external debt level and oil production

Abstract: Abstract. The article comprises theoretical discussion of the influence of the revenues obtained from the exploitation of oil reserves on the external debt level in the countries of the world. Econometric methods are applied to analyse statistical data for [2003][2004][2005][2006][2007][2008][2009][2010][2011][2012][2013][2014][2015][2016] and quantitative characteristics of this influence. It was concluded that rise in oil prices results in growth of the national external debt. We found that 1% growth in oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Although the paper of V. Marjanovic (2015) notes that the econometric approach to some extent simplifies the results of the structural analysis, we guess that this method is the most preferable for the achievement of the objectives of the paper. Application of econometric methods for conducting research is rather popular (Hasanli and Ismayilova, 2017) because such models are characterised by the presence of standard criteria indicators of their adequacy, the possibility of correct consideration of the modelled factors and convenience of implementation (Apokin et al, 2017). Moreover, we will use various indicators of the structural changes as the exogenous variables of the models.…”
Section: Methodsmentioning
confidence: 99%
“…Although the paper of V. Marjanovic (2015) notes that the econometric approach to some extent simplifies the results of the structural analysis, we guess that this method is the most preferable for the achievement of the objectives of the paper. Application of econometric methods for conducting research is rather popular (Hasanli and Ismayilova, 2017) because such models are characterised by the presence of standard criteria indicators of their adequacy, the possibility of correct consideration of the modelled factors and convenience of implementation (Apokin et al, 2017). Moreover, we will use various indicators of the structural changes as the exogenous variables of the models.…”
Section: Methodsmentioning
confidence: 99%
“…According to Yadulla Hasanli's research, oil revenues and oil price have an impact on foreign debt level. So 1% increasing in oil prices will increase foreign debt by 3.17% (Yadulla, H. 2017). Javier F. Mory has shown in his research that the rise or fall of oil prices during 1951-1990 had asymmetric impacts on production volumes and other macroeconomic indicators (Mory, J.F.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In their study "Econometric Model of Dependence between the Oil prices, and the Global National Debt Level and Oil Production", (Hasanli & Ismayilo, 2018) using Log linear data applied OLS, concluded that a rise in oil prices results into the growth of the world national debt, where they found that a 1% growth in oil prices increased the volume of foreign debt to World GDP by 3.17. But they fall short of isolating any particular country.…”
Section: Empirical Frameworkmentioning
confidence: 99%
“…The petroleum imports rose from around US$197 Million in 1980 to US$2.07 Billion in 2019 (COMSTAT, 2020). Additionally, however, other general macroeconomic variables, as determined in the study, equally continued to rise in the Zambian case with Government Expenditures rising from US$514.8 Million to US$2.5 Billion, GDP rising from US$4.3 to US$27.2 Billion, Gross Capital Formation rising from US$443.3 Million to US$ 9.7 Billion, Exports rising from US$ 942 Million to US$10.2 Billion, Non-Petroleum Imports rising from US$746.4 Million to Proceedings of the First Australian International Conference on Industrial Engineering andOperations Management, Sydney, Australia, December 20-21, 2022 Hasanli &Ismayilo (2018) using Log linear data applied OLS, and concluded that a rise in oil prices results into the growth of the world national debt, where they found that a 1% growth in oil prices increased the volume of foreign debt to World GDP by 3.17. But they fell short of isolating any particular country.…”
Section: Introductionmentioning
confidence: 99%